2006
DOI: 10.1152/japplphysiol.00064.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neural and hydroxyl radical mechanisms underlying laryngeal airway hyperreactivity induced by laryngeal acid-pepsin insult in anesthetized rats

Abstract: Laryngopharyngeal or gastroesophageal reflux is associated with laryngeal airway hyperreactivity (LAH), but neither the cause-effect relationship nor the underlying mechanism has been elucidated. Here we established a rat model with enhanced laryngeal reflex reactivity induced by laryngeal acid-pepsin insult and investigated the neural and hydroxyl radical (*OH) mechanisms involved. The laryngeal segments of 103 anesthetized rats were functionally isolated while animals breathed spontaneously. Ammonia vapor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 65 publications
4
41
0
Order By: Relevance
“…In these studies [14][16], these exaggerated responses could be prevented by pretreatment with antioxidants, indicating that there seemed to be an involvement of ROS in the sensitization of airway C-fibers and the development of airway hypersensitivity. However, questions remained as to whether the suppressive effects of the antioxidants in these studies resulted from a prevention of sensitization of the afferent fibers by the increased ROS or occurred because there was a removal of the basal function of ROS, which led to diminished afferent fiber sensitivity to these airway insults.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In these studies [14][16], these exaggerated responses could be prevented by pretreatment with antioxidants, indicating that there seemed to be an involvement of ROS in the sensitization of airway C-fibers and the development of airway hypersensitivity. However, questions remained as to whether the suppressive effects of the antioxidants in these studies resulted from a prevention of sensitization of the afferent fibers by the increased ROS or occurred because there was a removal of the basal function of ROS, which led to diminished afferent fiber sensitivity to these airway insults.…”
Section: Discussionmentioning
confidence: 86%
“…It has been previously shown that acute intermittent hypoxia [14] and laryngeal insult with acid and pepsin [15], [16] are able to potentiate the afferent and/or reflex responses of the airway C-fibers to stimulants in rats; the potentiating effect of the former and latter insults were found to be mediated through the TRPA1 and P2X receptors, respectively. In these studies [14][16], these exaggerated responses could be prevented by pretreatment with antioxidants, indicating that there seemed to be an involvement of ROS in the sensitization of airway C-fibers and the development of airway hypersensitivity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ROS not only sensitize the carotid sinus nerves but also the capsaicin-sensitive afferent fibers. Recent studies demonstrated that laryngeal acidpepsin insult can evoke laryngeal airway hyperreactivity through sensitization of the capsaicin-sensitive laryngeal afferent fibers by ROS (54,55). This concept is supported by the present finding that both AIH-enhanced reflex apnea and LVCF sensitivity to capsaicin and ␣,␤-methylene-ATP were significantly prevented by dimethylthiourea (a hydroxyl radical scavenger) or N-acetyl-L-cysteine (an antioxidant), so ROS may be a causative factor in the development of afferent hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a clinical issue in patients, whereby inconsistencies in histological patterns makes the diagnose difficult 26 . Different rat models investigating impacting factors on reflux laryngitis to mimic the human conditions were developed as there is the determination of the relationship between reflux and laryngeal hypersensitivity and the influence of pepsin 27 or the influence of bile reflux 28 …”
Section: Discussionmentioning
confidence: 99%